CONTINUOUSLY AND CYCLIC CASTING BY SILVERING OF PIPE SLUGS - E. I. Marukovich; V. F. Bevza; V. P. Grusha (Литьë и металлургия)
The description of the principally new effective highly-productive method of molding of tubular metalblocks without core application is provided. Analysis of formation of billets castings from high-chromium cast iron on the example of slugs of the detail “brake disk” of the cord twist machine is given, operational characteristics of the details are provided. The technical description of the foundry equipment is given.